2019
DOI: 10.1016/j.apsoil.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Soil ecosystem functions in a high-density olive orchard managed by different soil conservation practices

Abstract: The long-term effects of two different soil management practices, natural grass cover (NC) and conservation tillage (CT), on soil functions (carbon sequestration, habitat for organisms, and water movement and retention) were determined in a high-density, mature olive orchard (Olea europaea L. cv.Frantoio) growing in a sandy loam soil (Typic Haploxeralf) in a Mediterranean environment. Ten years after the beginning of the different soil management, soil samples were collected at 0-10 and 10-20 cm depth and at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 62 publications
3
39
0
Order By: Relevance
“…Pauropoda and Symphyla are two groups often reported together within the microarthropod community. Both groups generally show high sensitivity to stress in soil habitat and generally characterize undisturbed soils [149,150].…”
Section: Pauropoda and Symphylamentioning
confidence: 99%
See 2 more Smart Citations
“…Pauropoda and Symphyla are two groups often reported together within the microarthropod community. Both groups generally show high sensitivity to stress in soil habitat and generally characterize undisturbed soils [149,150].…”
Section: Pauropoda and Symphylamentioning
confidence: 99%
“…Some studies noted that species diversity and abundance decline in intensive agricultural systems; above all, differences have been observed between organic and conventional management, where hedgerows have proved to be important in maintaining biodiversity providing a refuge and a source of woodlice for Isopoda community [151,158]. Vignozzi et al [149] reported a higher presence of this group in the less impacted natural cover soil than in the conservational tillage soil, highlighting the high sensitivity of Isopoda to habitat stress. Different grassland management has different impact on Isopoda, which are sensitive to botanical composition not only for food but also for vegetation structure, with increased mortality resulting from simplification of the habitat [159]; so that cutting, for example, is a non-selective method that differs from grazing, where impact depends on the herbivores present [158,160].…”
Section: Isopodamentioning
confidence: 99%
See 1 more Smart Citation
“…In orchards, the presence of ground beetles on the soil surface over the entire growing season renders them highly sensitive to the long-term effects of plant protection products sprayed onto the trees [88]. Furthermore, Staphylinidae, one of the largest families of Coleoptera, includes species that are mostly predacious and have a role as biological regulators of crop pests [89]. Environmental conditions, wide-spectrum insecticides and soil management type have a significant effect on species richness and modify the dominance structures of the beetle communities [90].…”
Section: Beetlesmentioning
confidence: 99%
“…There is experimental evidence that soil property assessments can represent an effective approach to investigate the influence of soil management on water storage [10], or to evaluate the impact of different soil conservation practices on soil functions [11,12]. Such studies have increased our knowledge on the sustainable management of orchards, but further investigations are needed for specific arid areas of the Mediterranean basin.…”
Section: Introductionmentioning
confidence: 99%